Tertundanya Hukum Responsif dalam Penanganan Perambahan Hutan Lindung Gunung Slamet - Salsabil, Hilda Halnum; Handayani, Sri Wahyu (JUNCTO: Jurnal Ilmiah Hukum, 2025)
Encroachment on the protected forest of the western slope of Mount Slamet reflects the tension between environmental conservation efforts and the economic needs of local communities. Since the reform era, approximately 154 hectares of protected forest area have been illegally converted into agricultural land. This article analyzes the state’s legal response to this issue using a normative juridical method and a conceptual approach based on Nonet and Selznick’s theory of responsive law. The findings indicate that government responses, particularly through Perum Perhutani, remain administrative and temporary, without follow-up policies capable of addressing the root socio-ecological problems, such as legal access to land and meaningful community participation in forest governance. The novelty of this study lies in its critical analysis of the delayed implementation of responsive law due to a policy vacuum in justice-oriented regulation, as well as its emphasis on the need to integrate environmental law, agrarian reform, and social forestry within a transformative legal framework. This study underscores that law should function not merely as an instrument of control, but also as a means of empowerment and sustainable ecological justice.